(untitled) (ІННОВАЦІЙНА ЕКОНОМІКА, 2023)
Шишковський А.О., Бродовська О.Г. КЛЮЧОВІ АСПЕКТИ ТА ПРІОРИТЕТИ ПОВОЄННОГО РОЗВИТКУ ДЛЯ УКРАЇНИ Мета статті полягає в аналізі поточного стану справ української економіки, правової системи, а також позиції на світовій політичній арені, аби визначити пріоритетні кроки, які мають бути зроблені у повоєнний період першочергово, а також основні положення, які повинні бути взяті до уваги вже сьогодні. Методика дослідження. Теоретичною і методологічною основою статті є фундаментальні положення сучасної науки. У процесі дослідження використовувалися загальнонаукові та спеціальні методи, зокрема: індукція та дедукція – на етапі збору, систематизації та обробки необхідної інформації; аналіз та порівняння – у процесі виявлення відображення поточного стану справ української економіки; графічний – для візуалізації результатів дослідження; абстрактно-логічний – для формування теоретичних висновків. Результати дослідження. Проведено аналіз поточного стану розвитку української економіки. Обґрунтовано функціонування правової системи України в контексті євроінтеграції. Окреслено пріоритетні кроки України на шляху повоєнної відбудови. Розглянуто теоретичні засади та систематизовано сутнісні характеристики реформ країни на шляху до членства в ЄС: правоохоронних органів, судової системи, децентралізації, запровадження системи публічних онлайн-закупівель Prozorro тощо. Розкрито перелік необхідних процедур для отримання статусу кандидата України в ЄС. Наукова новизна результатів дослідження. Науково обґрунтовано сутність імплементації зобов’язань України для отримання статусу членства в ЄС. Запропоновано для успішної післявоєнної відбудови економіки України збільшити частку іноземних грантів до 40-50% у 2024‒2026 роках у структурі зовнішнього офіційного фінансування уряду України, що, на відміну від існуючого, дасть змогу диверсифікувати джерела фінансування. Практична значущість результатів дослідження. Обґрунтовані за результатами дослідження висновки і пропозиції можуть бути використані при визначенні стратегічного вектору України на шляху до членства в ЄС. Ключові слова: реформи, відбудова, повоєнний період, ЄС, державна політика, інституції, бюджет. Shyshkovskyi A.O., Brodovska O.Н. KEY ASPECTS AND PRIORITIES OF POST-WAR DEVELOPMENT FOR UKRAINE Purpose. The purpose of the article is to analyze the current state of affairs of the Ukrainian economy, the legal system, as well as the position on the world political arena, in order to determine the priority steps that should be taken in the post-war period as a priority, as well as the main provisions that should be taken into account already today. Methodology of research. The theoretical and methodological basis of the article is the fundamental provisions of modern science. General scientific and special methods were used in the research process, in particular: induction and deduction – at the stage of collecting, systematizing and processing the necessary information; analysis and comparison – in the process of identifying the reflection of the current state of affairs of the Ukrainian economy; graphic – for visualization of research results; abstract and logical – for the formation of theoretical conclusions. Results. An analysis of the current state of development of the Ukrainian economy was carried out. The functioning of the legal system of Ukraine in the context of European integration is substantiated. Ukraine’s priority steps on the way to post-war reconstruction are outlined. The theoretical foundations were considered and the essential characteristics of the country’s reforms on the way to EU membership were systematized: law enforcement agencies, the judicial system, decentralization, the introduction of the Prozorro online public procurement system, etc. The list of necessary procedures for obtaining the status of a candidate for Ukraine in the EU was revealed. Originality. The essence of the implementation of Ukraine’s obligations to obtain the status of EU membership has been scientifically substantiated. For the successful post-war reconstruction of Ukraine’s economy, it is proposed to increase the share of foreign grants to 40-50% in 2024‒2026 in the structure of external official financing of the government of Ukraine, which, unlike the existing one, will make it possible to diversify sources of financing. Practical value. Conclusions and proposals based on the results of the research can be used in determining the strategic vector of Ukraine on the way to EU membership. Key words: reforms, reconstruction, post-war period, EU, state policy, institutions, budget.